2011
DOI: 10.1371/journal.pone.0019774
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses by Sequencing of Transcriptomes during Skeletal Muscle Development between Pig Breeds Differing in Muscle Growth Rate and Fatness

Abstract: Understanding the dynamics of muscle transcriptome during development and between breeds differing in muscle growth is necessary to uncover the complex mechanism underlying muscle development. Herein, we present the first transcriptome-wide longissimus dorsi muscle development research concerning Lantang (LT, obese) and Landrace (LR, lean) pig breeds during 10 time-points from 35 days-post-coitus (dpc) to 180 days-post-natum (dpn) using Solexa/Illumina's Genome Analyzer. The data demonstrated that myogenesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
181
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(194 citation statements)
references
References 71 publications
12
181
1
Order By: Relevance
“…Because the early stages of gestation mark the onset of myogenesis (Zhao et al, 2011), it is reasonable to assume that differences in placental efficiency caused by different prenatal survival patterns will affect myogenesis and ultimately postnatal growth efficiency (Dwyer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Because the early stages of gestation mark the onset of myogenesis (Zhao et al, 2011), it is reasonable to assume that differences in placental efficiency caused by different prenatal survival patterns will affect myogenesis and ultimately postnatal growth efficiency (Dwyer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2011) confirmed that muscle regulatory factor (MRF) and MEF2 families are critical for the phenotypic differences between two pig breeds and proposed a novel model myogenesis. According to these authors, MyoD and MEF2A control the balance between intermuscular adiopogenesis and myogenesis by regulating the CCAAT/enhancerbinding protein (CEBP) family, while MEF2C and Myf5 are important during the whole myogenesis process and MEF2D affects muscle growth and maturation.…”
Section: Discussionmentioning
confidence: 68%
“…Many studies have shown that MEF2 transcripts were predominantly expressed in the muscle tissues of humans, mice, and pigs (Naya and Olson 1999;Potthoff et al, 2007;Liu et al, 2011). In skeletal muscle cells in culture, MEF2D has been reported to be expressed in proliferating myoblasts prior to the onset of differentiation (Breitbart et al, 1993) and to play a crucial role in muscle growth and maturation during porcine myogenesis (Zhao et al, 2011). Moreover, it has been reported that MEF2 proteins regulate the promoter activity of several negative regulators of myogenesis, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental approaches have revealed that MEF2 factors play an important role in the regulation of gluconeogenesis and adipocyte differentiation by regulating the expression of target genes, such as glucose transporter protein 4 (GLUT4) (Thai et al, 1998;Silva et al, 2005) and CCAAT/enhancer-binding protein α (C/EBPα) (Zhao et al, 2011) in skeletal muscle, heart, and adipose tissue. It has been shown that the level of GLUT4 expression is dependent on the binding of the MEF2A-MEF2D heterodimer complex to the MEF2 DNA-binding site in human and mice GLUT4 promoters; since a reduction in MEF2 expression is correlated with reduced GLUT4 promoter activity (Mora et al, 2001;Santalucia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%